Late Wisconsinan Glacial Geomorphology of the Kent Interlobate Complex, Ohio, USA - Santos,João Bessa (2012)
The northern sector of the Kent Interlobate Complex, created by two major ice lobes of the Laurentide Ice Sheet during late Wisconsinan times, dominates the glacial landscape of northeast Ohio. The geomorphology of this impressive complex reveals the presence of large hummocks, kettle lakes and substantial esker chains. The esker chains, usually smaller than 1.3 km long, run parallel to the Interlobate complex geographic orientation of northeast-southwest. Gravel pits present on large hummocks display bedded and sorted sedimentary units of gravel, sand and gravel and climbing ripple laminated sand with folds, which demonstrate that the northern sector of the Interlobate complex is primarily a glaciofluvial feature. Topping these hummocks is a massive clast-supported diamicton interpreted to be a debris flow. These geomorphic and sedimentary characteristics seem to indicate that hummocks present in the Interlobate area are in fact kames and that the entire northern sector of the interlobate complex is a product of late Wisconsinan time transgressive ice stagnation that occurred between two major ice lobes